Differential expression of genes mapping to recurrently abnormal chromosomal regions characterize neuroblastic tumours with distinct ploidy status - Acosta Sandra; Tuset Esperanza; Gerald William L; de Torres Carmen; Rodríguez Eva; Perez Noelia; Ríos José; Domenech Gema; Cheung Nai-Kong V; Mackintosh Carlos; Garcia Idoia; Lavarino Cinzia; et al. (BMC, 2008)
Abstract Background Neuroblastic tumours (NBTs) represent a heterogeneous spectrum of neoplastic diseases associated with multiple genetic alterations. Structural and numerical chromosomal changes are frequent and are predictive parameters of NBTs outcome. We performed a comparative analysis of the biological entities constituted by NBTs with different ploidy status. Methods Gene expression profiling of 49 diagnostic primary NBTs with ploidy data was performed using oligonucleotide microarray. Further analyses using Quantitative Real-Time Polymerase Chain Reaction (Q-PCR); array-Comparative Genomic Hybridization (aCGH); and Fluorescent in situ Hybridization (FISH) were performed to investigate the correlation between aneuploidy, chromosomal changes and gene expression profiles. Results Gene expression profiling of 49 primary near-triploid and near-diploid/tetraploid NBTs revealed distinct expression profiles associated with each NBT subgroup. A statistically significant portion of genes mapped to 1p36 (P = 0.01) and 17p13-q21 (P < 0.0001), described as recurrently altered in NBTs. Over 90% of these genes showed higher expression in near-triploid NBTs and the majority are involved in cell differentiation pathways. Specific chromosomal abnormalities observed in NBTs, 1p loss, 17q and whole chromosome 17 gains, were reflected in the gene expression profiles. Comparison between gene copy number and expression levels suggests that differential expression might be only partly dependent on gene copy number. Intratumoural clonal heterogeneity was observed in all NBTs, with marked interclonal variability in near-diploid/tetraploid tumours. Conclusion NBTs with different cellular DNA content display distinct transcriptional profiles with a significant portion of differentially expressed genes mapping to specific chromosomal regions known to be associated with outcome. Furthermore, our results demonstrate that these specific genetic abnormalities are highly heterogeneous in all NBTs, and suggest that NBTs with different ploidy status may result from different mechanisms of aneuploidy driving tumourigenesis.